2004
DOI: 10.1158/1078-0432.ccr-0604-3
|View full text |Cite
|
Sign up to set email alerts
|

Altered N-myc Downstream-Regulated Gene 1 Protein Expression in African-American Compared with Caucasian Prostate Cancer Patients

Abstract: Purpose: The protein encoded by N-myc downstreamregulated gene 1 (NDRG1) is a recently discovered protein whose transcription is induced by androgens and hypoxia. We hypothesized that NDRG1 expression patterns might reveal a biological basis for the disparity of clinical outcome of prostate cancer patients with different ethnic backgrounds.Experimental Design: Patients who underwent radical prostatectomy between 1990 and 2000 at Veterans Administration Medical Center of New York were examined. We studied 223 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 20 publications
3
35
0
Order By: Relevance
“…Conversely there was very little to no expression of NDRG1 protein in poorly differentiated cells, although we showed HIF-1a-positive nuclei in these regions. This observation was in agreement with studies of colorectal and prostatic cancer, in which NDRG1 was reduced in poorly differentiated adenocarcinoma compared to well-differentiated cells (van Belzen et al, 1997;Guan et al, 2000;Caruso et al, 2004). The difference being that, quiescent apical colonic epithelia express NDRG1, whereas normal pancreatic cell types do not.…”
Section: Discussionsupporting
confidence: 90%
“…Conversely there was very little to no expression of NDRG1 protein in poorly differentiated cells, although we showed HIF-1a-positive nuclei in these regions. This observation was in agreement with studies of colorectal and prostatic cancer, in which NDRG1 was reduced in poorly differentiated adenocarcinoma compared to well-differentiated cells (van Belzen et al, 1997;Guan et al, 2000;Caruso et al, 2004). The difference being that, quiescent apical colonic epithelia express NDRG1, whereas normal pancreatic cell types do not.…”
Section: Discussionsupporting
confidence: 90%
“…Drg-1 has also been shown to exert a similar metastasis-suppressive effect in colon cancer cells in a mouse model (3). Consistent with our in vivo results, we and others have found that expression of the Drg-1 gene is inversely correlated with Gleason grades in prostate cancer, and importantly, this downregulation is more significant in patients with metastasis to lymph nodes than those with organ-confined disease (2,4). Notably, we have observed similar inverse correlation of Drg-1 expression with metastasis in breast carcinoma patients (5).…”
Section: Introductionsupporting
confidence: 92%
“…Despite NDRG1 upregulation in many other tumor types [10,17,18,23] , NDRG1 expression in colorectal cancer has been controversial [2,19,20] . Wang et al [19] demonstrated that NDRG1 expression was increased in colorectal carcinogenesis and correlated with lymph node metastasis in a Chinese population and suggested that NDRG1 might be a possible marker for prediction of early metastasis of colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, disparity in the incidence and clinical progression of prostate cancer between African Americans and Caucasians had also been reported. When access to care as a possible confounding variable in disease outcome was controlled for, Caruso et al [23] demonstrated that African American patients presented with a significantly worse clinicopathological profile than Caucasian patients and that ethnicity was an independent factor in disease recurrence after surgical treatment. Interestingly, different expression patterns of the NDRG1 protein might reflect differences in the response of prostatic epithelium to hypoxia and androgens in African Americans compared with Caucasians, revealing a possible biological basis underlying the disparity in clinical outcomes of prostate cancer patients with different ethnic background [23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation